Unleashing the synergistic effect of promising fungicides: a breakthrough solution for combating powdery mildew in pea plants - Maria,; Naz, Ishrat; Khan, Rizwan; Alam, Syed Sartaj; Iqbal, Owais; Akram, Shazia; Rajput, Nasir Ahmed; Younas, Muhammad Usama; Qasim, Muhammad; Ali, Ijaz; Elsalahy, Heba H.; Iqbal, Rashid; et al. (Frontiers in Microbiology, 2024)
Pea powdery mildew, caused by Erysiphe pisi, is a major limitation to global pea production. The emergence of fungicide-resistant pathogen populations due to frequent and injudicious pesticide application highlights the importance of exploring the synergistic properties of fungicide combinations. This study investigated the efficacy of difenoconazole, thiophanate-methyl, and sulfur, both individually and in mixtures, against powdery mildew and assessed the interaction types between these fungicides. The results demonstrated that the combination of difenoconazole, thiophanate-methyl, and sulfur was the most effective in reducing, reducing disease severity to 6.10% and minimizing conidial production on foliage. Additionally, this fungicide combination reduced conidial germination by 89.26% in vitro and by 87.50% in a detached leaf assay compared to the control. The treatment also positively impacted leaf chlorophyll content (55.18), green pod yield (22.21 tons ha−1), seed yield (12.29 tons ha−1), and other yield-related parameters. Although statistically significant, this ternary fungicide combination was closely followed by the binary combination of thiophanate-methyl and sulfur, which was the only combination exhibiting synergism in both laboratory and field trials with a synergy factor (SF) > 1. In conclusion, this approach offers improved disease control as part of integrated disease management (IDM) while minimizing the risk of resistant pathogen strains.